Penerapan Model Pembelajaran Kooperatif Think Talk Write (TTW) dalam Pembelajaran Menulis Surat Pribadi pada Siswa Kelas VII SMP Pelita Kasih Kota Bengkulu - Marinir Tu Meilani Simanjuntak; Arono Arono; Noermanzah Noermanzah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
One way to improve students ability to write personal letters is to apply the think talk write cooperative learning model. The purpose of this study was to describe the learning process by applying the think talk write cooperative leraning model and to describe the learning outcomes using the think talk write cooperative learning model. The research method used is descriptive method with a qualitative approach. Data collection techniques using observation and documentation techniques. The data analysis technique in this study uses three steps in analyzing the data, namely reducing data, presenting data, and drawing conclusions or verification. Test the validity of the data using an inter rater and member check. The result showed that the steps of learning to write personal letters using the think talk write cooperative learning model, namely, think is done by giving reading matrial and asking students to write things that are considered important, talk is done by the teacher guiding students to conduct discussions about the results of student notes, and write is done by asking students to construct the results that have been obtained from the stages of think and talk. Then, the results of students ability to write personal letters by applying the think talk write cooperative learning model obtained and average value of 75,18 which was included in the sufficient category.